REIMAGINING ENGLISH LEARNING IN THE AI ERA: A WORLD OF POSSIBILITIES AND BARRIERS - Alek; Abdul Rabbi Arrasul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Among new possibilities and challenges that have emerged in the conditions of the AI era, the learning of English language experience significant changes that requires a reconsideration of classical approaches to teaching and learning. Nowadays, there have been developments in manners of AI technologies which create new opportunities for more functional models of personalized learning However, there are many barriers that continue to exist and block the further development of English language learners. The paradigm shifts of ELL are discussed in this paper, major gaps are identified and the latest technologies and practices in the field are also presented. In turn, the study aims at distinguishing crucial factors that contribute to the efficiency of AI supported learning paradigms encompassing adaptive learning, automatic feedback, and intelligent tutoring systems. Thus, the paper enriches the existing knowledge base with a new suggestion of an AI-enabled model of English language learning that targets the existing challenges and utilizes the possibilities of AI for improving learning conditions for all students. Through this model, educators and learners can avoid pitfalls inherent within the new age of Artificial Intelligence, thus providing a fulfilment of a teaching and learning model in the present society